Convenient and high-yielding strategy for preparing nano-ZnMn2O4 as anode material in lithium-ion batteries. (20th April 2016) - Zhang, Tong; Gao, Yu; Yue, Huijuan; Qiu, Hailong; Guo, Zhendong; Wei, Yingjin; Wang, Chunzhong; Chen, Gang; Zhang, Dong
Graphical abstract: A convenient combustion assist coprecipitation approach to synthesis nano-ZnMn2O4 anode material with excellent electrochemical performance. Highlights: ZnMn2 O4 material has been gained from a novel combustion approach. The ZnMn2 O4 generated at 800 °C exhibits the best electrochemical performance. This convenient method enables scale-up production of transition metal oxides. Abstract: Time and energy saving synthesis method is crucial to the scale up applications of energy conversion and storage materials. In this report, we demonstrate a convenient and novel approach to fabricate the highly crystalline ZnMn2 O4 nanoparticles as anode materials for Li rechargeable batteries. Pure phase ZnMn2 O4 samples can be feasibly obtained under different calcination temperature from the precursor via combustion assisted coprecipitation method. Various techniques are used to characterize the structure and morphology of the products. Sample gained at 800 °C exhibits the best electrochemical property for lithium ion batteries. A reversible specific capacity of 716 mAh g −1 can be retained under a current density of 100 mA g −1 after 90 circles. Even the current density elevated up to 1000 mA g −1, the reversible capacity of the material still can be kept as high as 500 mAh g −1 after 1200 cycles. The outstanding performance compared to the other samples benefits from its good crystallinity and uniform dispersion with appropriate particle size.